Polymer modified soil composite impermeable material and on-site heat-source-free synthesis method thereof
Through the use of oxidation and reduction between the pussy layer, the aggregation monomer aggregation caused by the system, which solved the problem of anti -seepage performance of existing pussy soil reform methods under corrosive conditions. Composite anti -seepage materials have excellent anti -seepage performance and simplified process.
Patent Information
- Application Number
- CN202411459798.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing bentonite modification methods have significantly reduced anti-seepage performance under corrosive conditions such as high salt, strong acid, and strong alkali. The process is complex and the cost is high, making it difficult to prepare on a large scale directly on the engineering site.
The use of oxidation reduction caused by the system at room temperature or even low temperature caused a polymer to aggregate at the original position between the pushing soil layer, prepare the polymer modified soil composite anti -seepage material, avoid the heating and drying process, and simplify the process.
The direct synthetic polymer modified soil composite anti -seepage material is achieved in the case of no heat source, which has excellent anti -seepage performance, low cost, and large -scale preparation for engineering site.
Smart Images

Figure CN119349935A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental geotechnical engineering, and in particular to a polymer-modified soil composite anti-seepage material and an on-site heat-source-free synthesis method thereof. Background Art
[0002] The main component of bentonite is montmorillonite crystals, with a chemical composition of Al2O3·4SiO2·3H2O. It is a 2:1 type layered aluminosilicate composed of two layers of silicon-oxygen tetrahedrons sandwiching a layer of aluminum-oxygen octahedrons. The octahedrons and tetrahedrons are connected by shared oxygen atoms. The geometric space between the montmorillonite crystal layer structure is called the interlayer domain, with a width of 0.96 to 2.14 nm. This layer stacking structure makes the specific surface area of bentonite as high as 600 to 800 m 2 / g. According to the different cations in the interlayer domain, bentonite is divided into calcium-based bentonite, sodium-based bentonite and sodium calcium-based bentonite. The surface of bentonite is negatively charged, and water or other polar molecules can be adsorbed into the interlayer domain through weak interactions, so that the interlayer domain of montmorillonite is expanded. As the number of water molecules adsorbed between the layers increases, the montmorillonite sheets gradually separate and osmotic swelling occurs, which is manifested macroscopically as the volume expansion of bentonite particles. Due to the high specific surface area and high expansion multiple of bentonite, it is often used as the core material of anti-seepage and pollution interception materials (such as soil-bentonite vertical barrier walls, geosynthetic clay liners (GCL), compacted clay liners, etc.) in environmental geotechnical engineering. It is widely used in industrial solid waste landfills, domestic waste landfills, tailings ponds and various polluted sites to prevent the migration of pollutants within the site and avoid pollution to the surrounding environment. However, the water absorption and expansion performance of natural bentonite materials is significantly reduced under corrosive conditions such as high salt, strong acid, and strong alkali, resulting in a significant deterioration of its anti-seepage barrier performance and an inability to form an effective anti-fouling barrier. It needs to be modified to achieve an effective anti-seepage effect.
[0003] There are two main ways to modify bentonite: bentonite-polymer physical blending modification and bentonite in-situ polymerization modification. Bentonite-polymer physical blending refers to mixing bentonite and hydrophilic polymer in a dry state to obtain a bentonite-polymer composite material (BPC). When BPC is used for anti-seepage barrier, the polymer absorbs water and swells in water or salt solution to form a gel, which fills the gaps between bentonite particles, making the composite material denser and achieving a good anti-seepage effect. Tian et al. (K. Tian, WJ Likos, CH Benson. Polymer Elution and Hydraulic Conductivity of Bentonite-Polymer Composite Geosynthetic Clay Liners. Journal of Geotechnical and Geoenvironmental Engineering, 2019, 145(10): 04019071) tested the anti-seepage performance of GCL made of BPC and natural sodium bentonite (NaB), respectively. The results showed that the permeability coefficient of BPC GCL to chemical solution was 1 to 4 orders of magnitude lower than that of NaB GCL. SEM images showed that the blockage of bentonite pores by polymer hydrogel was the reason for the lower permeability coefficient of BPC GCL. The physical blending method can make up for the disadvantage of insufficient swelling of bentonite particles in chemical solutions, but the interface between bentonite and polymer in BPC materials is weak, and serious polymer elution problems are prone to occur in actual engineering use, that is, the polymer is separated from the pores of bentonite, which greatly deteriorates its anti-seepage barrier properties (C. Wire, T. Abichou. Investigating Factors Influencing Polymer Elution And The Mechanism Controlling The Chemical Compatibility Of GCLs Containing Linear Polymers. Geotextiles and Geomembranes, 2021, 49 (4): 1004-1018). In-situ polymerization modification of bentonite refers to inserting monomers, initiators and catalysts into the interlayers of montmorillonite crystals, and then initiating monomer polymerization. The polymer overcomes the Coulomb force between the montmorillonite sheets and stretches them open to obtain intercalated or even exfoliated polymer in-situ modified bentonite.The in-situ polymerization modified bentonite has excellent anti-seepage performance and is not prone to polymer elution like BPC. However, since free radicals are highly sensitive to oxygen, they are usually synthesized under an inert environment, and the in-situ preparation process requires the bentonite raw materials, which are originally in a dry powder state, to be re-wetted, stirred, heated, reacted, dried, crushed, screened, and other processes. The operation is cumbersome and time-consuming, costly, and only suitable for factory production. The crushing process will also destroy the polymer network between the montmorillonite flakes, thereby affecting the anti-seepage performance of the polymer-modified bentonite anti-seepage material.
[0004] In summary, it is necessary to invent a new modification method that can avoid the shortcomings of the above two types of modification methods and combine the advantages of the two methods, that is, a polymer-modified bentonite solution that has a simple preparation process, excellent anti-seepage performance, is not prone to polymer elution, and is suitable for large-scale direct preparation at engineering sites. Summary of the invention
[0005] In order to solve the above problems, the present invention provides an on-site heat-source-free synthesis method of a polymer-modified soil composite anti-seepage material. The method utilizes a redox initiation system to generate free radicals at room temperature or even low temperature, and can initiate in-situ polymerization of polymerization monomers between bentonite layers without additional heating. The reducing agent can consume the oxygen in the reaction system, so the polymerization process does not need to be carried out under an inert atmosphere. At the same time, the resulting product does not need to undergo drying, crushing, screening and other procedures before it can be directly poured into an anti-seepage barrier. The preparation process is simple, the anti-seepage performance is excellent, the cost is low, and there is no need for pre-production in a factory, but it is suitable for large-scale preparation directly on the engineering site.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a formula of a polymer-modified soil composite anti-seepage material, comprising the following raw materials: water, anionic polymer monomer A, polymer monomer B containing a hydrophilic group, a crosslinking agent, bentonite, an initiator, and a filler.
[0008] Preferably, the anion of the anionic polymerizable monomer A comprises at least one of a sulfonate group and a carboxylate group;
[0009] The carboxylate group includes at least one of acrylate, methacrylate and maleate.
[0010] Preferably, the hydrophilic group of the polymeric monomer B containing a hydrophilic group comprises at least one of an amino group and a quaternary amino group.
[0011] Preferably, the anionic polymerizable monomer A comprises at least one of sodium acrylate and sodium methacrylate;
[0012] The polymerizable monomer B includes at least one of 2-acrylamide-2-methylpropanesulfonic acid and dimethylaminoethyl acrylate.
[0013] Preferably, the crosslinking agent includes at least one of N,N'-vinylbisacrylamide, N,N'-methylenebisacrylamide, diacetone acrylamide, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, caprolactone acrylate, alginate acrylate, and divinylbenzene.
[0014] Preferably, the bentonite includes at least one of sodium-based bentonite, calcium-based bentonite, and sodium-calcium-based bentonite.
[0015] Preferably, the initiator is a redox initiator, the redox initiator comprises an oxidant and a reductant, the oxidant comprises at least one of hydrogen peroxide, persulfate, and hydroperoxide;
[0016] The reducing agent includes at least one of ferrous salt, cuprous salt, sodium bisulfite, sodium sulfite, sodium thiosulfate, alcohol, amine, oxalic acid, and glucose;
[0017] The mass ratio of the oxidant to the reductant is (0.05-10):1;
[0018] And / or, the filler includes at least one of graded fine sand, graded tailings sand, graded silt, graded construction waste, and graded engineering slag; the average particle size d of the filler is 50 It is 0.1mm~1mm.
[0019] Preferably, the mass ratio of the water to the bentonite is (0.5-10):1;
[0020] The mass ratio of the anionic polymerizable monomer A to the polymerizable monomer B containing a hydrophilic group is (10-800):30;
[0021] The mass ratio of the anionic polymerizable monomer A to the crosslinking agent is (100-900):1;
[0022] The mass ratio of the initiator to the anionic polymerization monomer A is (0.05-5):100;
[0023] The mass ratio of the filler to the bentonite is (0-90):10;
[0024] The mass ratio of the anionic polymerizable monomer A to the water is (5-20):100.
[0025] In a second aspect, the present invention further provides an on-site heat-source-free synthesis method of the polymer-modified soil composite anti-seepage material, comprising the following steps:
[0026] Water, anionic polymer monomer A, polymer monomer B containing hydrophilic groups, crosslinking agent, bentonite, initiator and filler are mixed and reacted to obtain polymer modified soil composite anti-seepage material.
[0027] Preferably, the reaction temperature is 5-60°C.
[0028] The polymer modified soil composite anti-seepage material and the on-site heat source-free synthesis method thereof of the present invention have the following beneficial effects compared with the prior art:
[0029] 1. The present invention provides a method for directly synthesizing a polymer-modified soil composite anti-seepage material without a heat source at a construction site, using a redox initiation system to replace the thermal initiation system of the existing traditional polymer-modified bentonite synthesis method. On the one hand, the redox initiation system causes the initiator to generate free radicals through redox action, and its activation energy is greatly reduced, so that free radicals that initiate monomer polymerization can be generated at a lower temperature, which can be suitable for preparation without a heat source at the construction site; on the other hand, the reducing agent in the redox initiation system can consume oxygen in the reaction system, so that free radicals that are highly sensitive to oxygen can normally initiate polymerization, so that the polymerization process does not need to be carried out under an inert atmosphere;
[0030] 2. The on-site heat-source-free synthesis method of the polymer-modified soil composite anti-seepage material provided by the present invention does not require drying, crushing, screening and other processes in its preparation process. On the one hand, the drying and crushing processes will destroy the polymer network structure, thereby affecting the anti-seepage barrier performance of the material; on the other hand, the series of processes such as drying, crushing, screening, etc. are time-consuming, energy-consuming, and costly, especially when large-scale preparation is carried out, it is extremely difficult to quickly crush and screen the product. The polymer-modified bentonite anti-seepage material prepared according to the present invention can be directly applied to the anti-seepage barrier system, greatly reducing the number of procedures, reducing costs, shortening time, and improving efficiency, and the test results show that it has excellent anti-seepage barrier performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 Schematic diagram of the reaction mechanism of polymer-modified bentonite in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.
[0036] The embodiment of the present application provides a polymer-modified soil composite anti-seepage material, which includes the following raw materials: water, anionic polymer monomer A, polymer monomer B containing hydrophilic groups, a cross-linking agent, bentonite, an initiator, and a filler.
[0037] In some embodiments, the anion of the anionic polymerizable monomer A comprises at least one of a sulfonate group and a carboxylate group;
[0038] The carboxylate group includes at least one of acrylate, methacrylate and maleate.
[0039] In some embodiments, the hydrophilic group of the polymerized monomer B containing a hydrophilic group includes at least one of an amino group and a quaternary amino group.
[0040] In some embodiments, the anionic polymerizable monomer A includes at least one of sodium acrylate and sodium methacrylate;
[0041] The polymerizable monomer B includes at least one of 2-acrylamide-2-methylpropanesulfonic acid and dimethylaminoethyl acrylate.
[0042] Specifically, the anions in the anionic polymerizable monomer A can generate electrostatic interactions with the cations between the montmorillonite sheets and be adsorbed into the interlayer domain of the montmorillonite to achieve the purpose of in-situ polymerization. The hydrophilic group of the hydrophilic group polymerizable monomer B is at least one of an amino group and a quaternary amino group; the hydrophilic group is an atomic group that is easily affinity with water, which can greatly improve the hydrophilicity of the polymer modified bentonite, thereby improving the anti-seepage barrier performance of the modified bentonite.
[0043] In some embodiments, the crosslinking agent includes at least one of N,N'-vinylbisacrylamide, N,N'-methylenebisacrylamide, diacetone acrylamide, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, caprolactone acrylate, alginate acrylate, and divinylbenzene. The crosslinking agent and the polymer form a crosslinked network through covalent bonds, which can increase the stability and mechanical strength of the polymer.
[0044] In some embodiments, the bentonite includes at least one of sodium bentonite, calcium bentonite, and sodium calcium bentonite.
[0045] In some embodiments, the initiator is a redox initiator, the redox initiator comprises an oxidant and a reductant, the oxidant comprises at least one of hydrogen peroxide, a persulfate (such as ammonium persulfate), and a hydroperoxide;
[0046] The reducing agent includes at least one of ferrous salt, cuprous salt, sodium bisulfite, sodium sulfite, sodium thiosulfate, alcohol, amine, oxalic acid, and glucose;
[0047] The mass ratio of the oxidant to the reductant is (0.05-10):1.
[0048] Specifically, the redox initiator has a low activation energy and can generate free radicals at a relatively low temperature, thereby initiating in situ polymerization of the monomer without heating. At the same time, the reducing agent will also consume oxygen in the system, so that the polymerization process does not need to be carried out under an inert atmosphere.
[0049] In some embodiments, the filler includes at least one of graded fine sand, graded tailings sand, graded silt, graded construction waste, and graded engineering slag; the average particle size of the filler is d 50 It is 0.1mm~1mm.
[0050] In some embodiments, the filler is at least one of graded fine sand, graded tailings sand, graded silt, graded construction waste, and graded engineering slag, and its maximum particle size is less than 3 mm and the average particle size is d 50 It is between 0.1mm and 1mm, and has good grading (uniformity coefficient Cu>6, grading coefficient Cc is between 1 and 3).
[0051] In some embodiments, the mass ratio of water to bentonite is (0.5-10):1;
[0052] The mass ratio of the anionic polymerizable monomer A to the polymerizable monomer B containing a hydrophilic group is (10-800):30;
[0053] The mass ratio of anionic polymerization monomer A to crosslinking agent is (100-900):1;
[0054] The mass ratio of the initiator to the anionic polymerization monomer A is (0.05-5):100;
[0055] The mass ratio of filler to bentonite is (0-90):10;
[0056] The mass ratio of anionic polymerization monomer A to water is (5-20):100.
[0057] Based on the same inventive concept, the present invention also provides an on-site heat-source-free synthesis method of the above-mentioned polymer-modified soil composite anti-seepage material, comprising the following steps:
[0058] Water, anionic polymer monomer A, polymer monomer B containing hydrophilic groups, crosslinking agent, bentonite, initiator and filler are mixed and reacted to obtain polymer modified soil composite anti-seepage material.
[0059] In some embodiments, the reaction temperature is 5-60°C.
[0060] In some embodiments, the on-site heat-source-free synthesis method of the above-mentioned polymer-modified soil composite anti-seepage material comprises the following steps: adding water, anionic polymerization monomer A, polymerization monomer B containing hydrophilic groups, cross-linking agent, bentonite, initiator, and filler into a reaction container, mixing and stirring thoroughly until uniform, and pouring the mixture directly into the bottom lining anti-seepage layer, the top covering anti-seepage layer, the vertical barrier wall and other anti-seepage barriers, and after sufficient reaction, a polymer-modified soil composite anti-seepage material with excellent anti-seepage performance can be obtained.
[0061] The invention provides a method for directly synthesizing a polymer-modified soil composite anti-seepage material without a heat source on a construction site. A redox initiation system is used to replace the thermal initiation system of an existing traditional polymer-modified bentonite synthesis method. On the one hand, the redox initiation system causes an initiator to generate free radicals through redox action, and its activation energy is greatly reduced, so that free radicals initiating monomer polymerization can be generated at a lower temperature, and the method is suitable for preparation without a heat source on the construction site. On the other hand, the reducing agent in the redox initiation system can consume oxygen in the reaction system, so that free radicals highly sensitive to oxygen can normally initiate polymerization, and the polymerization process does not need to be carried out under an inert atmosphere. The on-site heat-source-free synthesis method of the polymer-modified soil composite anti-seepage material provided by the invention does not require drying, crushing, screening and other processes in its preparation process. On the one hand, the drying and crushing processes will destroy the polymer network structure, thereby affecting the anti-seepage barrier performance of the material. On the other hand, the series of processes such as drying, crushing, screening and other processes are time-consuming, energy-consuming and costly, and particularly when large-scale preparation is carried out, rapid crushing and screening of the product is extremely difficult. The polymer modified bentonite anti-seepage material prepared according to the present invention can be directly applied to the anti-seepage barrier system, which greatly reduces the number of processes, reduces costs, shortens time, and improves efficiency. Test results show that the anti-seepage barrier performance is excellent.
[0062] The following further describes the on-site heat-free synthesis method of the polymer-modified soil composite anti-seepage material of the present application with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. If not specifically stated, the technical means adopted in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0063] Example 1
[0064] The present application provides an on-site heat-source-free synthesis method of a polymer-modified soil composite anti-seepage material, comprising the following steps:
[0065] Add 100 mL of water to a three-mouth reaction kettle, then add 16.826 g of sodium acrylate, 2.46 g of 2-acrylamide-2-methylpropane sulfonic acid, 0.058 g of triethylene glycol dimethacrylate, and then add 45 g of sodium calcium-based bentonite (without fillers such as graded sand), stir thoroughly, add 0.289 g of ammonium persulfate and 0.289 g of sodium bisulfite and stir until uniform, and react fully at room temperature (25°C) to obtain the synthesized polymer-modified soil composite anti-seepage material.
[0066] Example 2
[0067] The present application provides an on-site heat-source-free synthesis method of a polymer-modified soil composite anti-seepage material, comprising the following steps:
[0068] Add 1L of water to a three-mouth reactor, then add 130.85g of sodium methacrylate, 19.13g of dimethylaminoethyl acrylate, 0.45g of N-N'methylenebisacrylamide, and then add 450g of sodium calcium bentonite, 3600g of graded sand (average particle size d 50 Between 0.1mm and 1mm, with good gradation, uneven coefficient Cu>6, gradation coefficient Cc between 1 and 3), after fully stirring, add 02.25g hydrogen peroxide and 02.25g sodium thiosulfate and stir until uniform, and fully react at room temperature (25°C) to obtain the synthesized polymer modified soil composite anti-seepage material.
[0069] Example 3
[0070] The present application provides an on-site heat-source-free synthesis method of a polymer-modified soil composite anti-seepage material, comprising the following steps:
[0071] Add 100 mL of water to the three-mouth reactor, then add 9.8154 g of sodium methacrylate, 1.435 g of dimethylaminoethyl acrylate, 0.034 g of N-N'methylenebisacrylamide, and then add 45 g of sodium calcium bentonite, 270 g of graded tailings sand (average particle size d 50 Between 0.1mm and 1mm, with good gradation, uneven coefficient Cu>6, gradation coefficient Cc between 1 and 3), after fully stirring, add 0.169g hydrogen peroxide and 0.169g sodium thiosulfate and stir until uniform, and fully react at room temperature (25°C) to obtain the synthesized polymer modified soil composite anti-seepage material.
[0072] Comparative Example 1
[0073] This comparative example provides a method for synthesizing a polymer-modified bentonite anti-seepage material, comprising the following steps:
[0074] Under a nitrogen atmosphere, 100 mL of water was added to a three-mouth reaction kettle, followed by 16.826 g of sodium acrylate, 2.46 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.058 g of triethylene glycol dimethacrylate, and then 45 g of sodium calcium-based bentonite. After sufficient stirring, 0.578 g of ammonium persulfate was added and stirred until uniform. The reaction kettle was placed in a 70 ° C oil bath pot for sufficient reaction, and the reaction product was taken out, dried, ground, and sieved. The polymer-modified bentonite was uniformly mixed in a mass ratio of 1:1 with a mesh size of 100 to 200 mesh and above 200 mesh, to obtain a polymer-modified bentonite anti-seepage material.
[0075] The preparation method of the polymer-modified bentonite in this comparative example is basically the same as that in Example 1, except that this comparative example does not use a redox initiation system, but instead initiates polymerization by heating, and needs to ensure that the reaction system is an anaerobic environment, and needs to dry, crush, and sieve the product to obtain the polymer-modified bentonite anti-seepage material.
[0076] Comparative Example 2
[0077] This comparative example provides a method for synthesizing a polymer-modified bentonite anti-seepage material, comprising the following steps:
[0078] 5.13 mL (3 g) of acrylic acid and 8.7 mL of 0.2 g / mL sodium hydroxide were added to 36.3 mL of water. After acid-base neutralization, 0.04 g of N, N'-vinylbisacrylamide and 3 g of N, N'-diethylacrylamide were added and stirred until completely dissolved. 60 g of calcium-based bentonite was added and stirred vigorously under a nitrogen atmosphere to mix the solution and bentonite evenly. 0.108 g of ammonium persulfate was added and reacted at room temperature for 3 h to obtain a product. The product was dried, crushed and sieved to obtain a polymer-modified bentonite anti-seepage material.
[0079] The preparation method of the polymer-modified bentonite described in this comparative example is similar to that in Example 1 in that no heating is required to initiate the polymerization reaction. The differences are: 1) the initiation mechanisms of the two are different; 2) this comparative example requires a series of operations such as drying, grinding, and screening of the product to obtain a polymer-modified bentonite anti-seepage material that can be used in engineering.
[0080] Comparative Example 3
[0081] This comparative example provides a method for synthesizing a polymer-modified bentonite anti-seepage material, comprising the following steps:
[0082] Add 18.8 mL of acrylic acid and 38.8 mL of 0.2 g / mL sodium hydroxide to 111 mL of water. After acid-base neutralization, add 0.1 g of N-N'vinyl bisacrylamide and stir until completely dissolved. Add 60 g of calcium-based bentonite and stir vigorously under a nitrogen atmosphere to mix the solution and bentonite evenly. Add 0.36 g of ammonium persulfate, raise the temperature to 70°C, react for 3 hours to obtain a product, dry, crush and sieve the product to obtain a polymer-modified bentonite anti-seepage material.
[0083] The preparation method of the polymer-modified bentonite described in this comparative example is different from that in Example 1 in that: 1) the initiation mechanisms of the two are different, and 2) the comparative example requires a series of operations such as drying, grinding, and screening of the product to obtain a polymer-modified bentonite anti-seepage material that can be used in engineering.
[0084] Performance Testing
[0085] The permeability coefficient of the polymer modified bentonite was tested using deionized water, sodium hydroxide solution (pH = 12), nitric acid solution (pH = 3) and artificially synthesized coal combustion product leachate (ionic strength I = 178mM), wherein the coal combustion product leachate was synthesized by dissolving reagent grade CaSO4, Na2SO4, MgSO4, K2SO4, NaCl and CaCl2 in deionized water, and its chemical composition is shown in Table 1; the permeability coefficient was determined by a flexible wall permeability test, and the determination method was based on the precipitation head constant water tail method in the standard ASTM D5084 formulated by the American Society for Testing and Materials. The permeability coefficients of the polymer modified bentonite anti-seepage materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 2.
[0086] Table 1 - Chemical composition of coal combustion product leachate
[0087]
[0088] Table 2- Permeability coefficients of anti-seepage materials prepared in different embodiments
[0089]
[0090] The preparation methods of the anti-seepage materials in Examples 1 to 3 and Comparative Examples 1 to 3 are compared as shown in Table 3 below.
[0091] Table 3 - Comparison of preparation methods of anti-seepage materials in different embodiments
[0092]
[0093]
[0094] It can be seen from Table 2 that the permeability coefficients of the four different permeates in the embodiments and comparative examples are all lower than the 5×10 -11m / s, and the anti-seepage performance of the embodiment is better than that of the comparative example. Comparative Examples 1 and 3 use a thermal initiation system, as shown in Table 3, and the preparation process needs to ensure an inert atmosphere, and the initiator is decomposed by heating to generate free radicals to initiate polymerization, and the product needs to be dried, crushed, and sieved before the modified bentonite anti-seepage material can be obtained. The preparation process is cumbersome, time-consuming and energy-consuming, and the cost is high, and it is not suitable for large-scale preparation on the engineering site. In comparison, the present invention has more advantages, that is, the redox initiation system is used to reduce the reaction activation energy, so that the synthesis can be carried out without a heat source, and the reducing agent can react with oxygen to ensure the activity of the free radicals that are highly sensitive to oxygen in the reaction system. After synthesis, there is no need for drying, crushing, and sieving, and it can be directly applied to the anti-seepage and anti-fouling barrier on the engineering site, with more excellent anti-seepage barrier performance, and its permeability coefficient is about 10 times lower than that of Comparative Examples 1 and 3. In Comparative Example 2, a free radical reaction accelerator is selected to decompose the initiator to produce free radicals. No heating is required, but it is necessary to ensure that the preparation is carried out under an inert atmosphere, and the product needs to be dried, crushed, and sieved. According to the permeability coefficient measurement results in Table 2, the permeability coefficient of Example 1 is significantly lower than that of Comparative Example 2, which indicates that the drying, crushing, and screening processes will have an adverse effect on the anti-seepage performance. Further, it is speculated that the drying and crushing processes will destroy the polymer network structure and reduce the structural integrity of the composite material. In contrast, the present invention has more excellent anti-seepage barrier properties.
[0095] Furthermore, Figure 1 Schematic diagram of the reaction mechanism of polymer-modified bentonite in Example 1 of the present invention.
[0096] from Figure 1 It can be seen that the Na + , Ca 2+ Electrostatic adsorption is produced, and the polymerizable monomer 2-acrylamide-2-methylpropanesulfonic acid containing hydrophilic groups and the cross-linking agent triethylene glycol dimethacrylate are uniformly dispersed in the montmorillonite layer domains. At the same time, the redox initiation system generates free radicals in the initiator (NH4)2S2O8 through redox action and initiates the polymerization of the monomers between the montmorillonite layer domains. A polymer network is formed under the action of the cross-linking agent to obtain a polymer in-situ modified bentonite nanocomposite anti-seepage material.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polymer modified soil composite anti-seepage material, characterized in that: The invention comprises the following raw materials: water, anionic polymer monomer A, polymer monomer B containing hydrophilic groups, crosslinking agent, bentonite, initiator and filler.
2. The polymer modified soil composite anti-seepage material according to claim 1, characterized in that: The anion of the anionic polymerizable monomer A includes at least one of a sulfonate group and a carboxylate group; The carboxylate group includes at least one of acrylate, methacrylate and maleate.
3. The polymer modified soil composite anti-seepage material according to claim 2, characterized in that: The hydrophilic group of the hydrophilic group-containing polymer monomer B includes at least one of an amino group and a quaternary amino group.
4. The polymer modified soil composite anti-seepage material according to claim 3, characterized in that: The anionic polymerizable monomer A includes at least one of sodium acrylate and sodium methacrylate; The polymerizable monomer B includes at least one of 2-acrylamide-2-methylpropanesulfonic acid and dimethylaminoethyl acrylate.
5. The polymer modified soil composite anti-seepage material according to claim 1, characterized in that: The crosslinking agent includes at least one of N,N'-vinylbisacrylamide, N,N'-methylenebisacrylamide, diacetone acrylamide, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, caprolactone acrylate, alginate acrylate and divinylbenzene.
6. The polymer modified soil composite anti-seepage material according to claim 1, characterized in that: The bentonite includes at least one of sodium-based bentonite, calcium-based bentonite, and sodium-calcium-based bentonite.
7. The polymer modified soil composite anti-seepage material according to claim 1, characterized in that: The initiator is a redox initiator, the redox initiator comprises an oxidant and a reductant, the oxidant comprises at least one of hydrogen peroxide, persulfate, and hydroperoxide; The reducing agent includes at least one of ferrous salt, cuprous salt, sodium bisulfite, sodium sulfite, sodium thiosulfate, alcohol, amine, oxalic acid, and glucose; The mass ratio of the oxidant to the reductant is (0.05-10):1; And / or, the filler includes at least one of graded fine sand, graded tailings sand, graded silt, graded construction waste, and graded engineering slag; the average particle size d of the filler is 50 It is 0.1mm~1mm.
8. The polymer modified soil composite anti-seepage material according to claim 1, characterized in that: The mass ratio of the water to the bentonite is (0.5-10):1; The mass ratio of the anionic polymerizable monomer A to the polymerizable monomer B containing a hydrophilic group is (10-800):30; The mass ratio of the anionic polymerizable monomer A to the crosslinking agent is (100-900):1; The mass ratio of the initiator to the anionic polymerization monomer A is (0.05-5):100; The mass ratio of the filler to the bentonite is (0-90):10; The mass ratio of the anionic polymerizable monomer A to the water is (5-20):
100.
9. An on-site heat-free synthesis method of a polymer-modified soil composite anti-seepage material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Water, anionic polymer monomer A, polymer monomer B containing hydrophilic groups, crosslinking agent, bentonite, initiator and filler are mixed and reacted to obtain polymer modified soil composite anti-seepage material.
10. The on-site heat-source-free synthesis method of the polymer-modified soil composite anti-seepage material according to claim 9, characterized in that: The reaction temperature is 5-60°C.
Citation Information
Patent Citations
Polymer modified bentonite foam stabilizer and preparation method thereof
CN113388382A
Polymer bentonite composite anti-seepage material and heat-source-free synthesis method thereof
CN113428870A